2010
DOI: 10.1111/j.1600-0501.2010.02000.x
|View full text |Cite
|
Sign up to set email alerts
|

Are panoramic images reliable in planning sinus augmentation procedures?

Abstract: Based on the present data, cone-beam CT imaging can be recommended for visualising anatomical structures during planning of sinus augmentation procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
48
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 27 publications
3
48
1
2
Order By: Relevance
“…On multi‐slice CT images, Temmerman et al. () observed that in one‐third of cases additional bony canals in the upper canine region started palatally and coursed in a latero‐cranial direction. In our study, prevalence of additional canals was much lower (nearly 16%) and included other locations than just canine region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On multi‐slice CT images, Temmerman et al. () observed that in one‐third of cases additional bony canals in the upper canine region started palatally and coursed in a latero‐cranial direction. In our study, prevalence of additional canals was much lower (nearly 16%) and included other locations than just canine region.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional radiographs may fail to properly display these anatomical configurations (Kohavi ; Temmerman et al. ) and even anatomy textbooks may lack detailed description of these variations.…”
mentioning
confidence: 99%
“…Visibility on panoramic images is limited and dependent on projection geometry, Kopecka et al head positioning and image magnification (6,19). However, several authors have indicated that panoramic radiographs can be a suitable diagnostic tool for vertical measurements when the patient is correctly positioned (20)(21)(22)(23)(24) because the vertical magnification factor, in contrast to the horizontal, is very consistent (6,16,19,23). The present study demonstrates that panoramic radiography is a sufficiently accurate method for interantral bone height imaging in the incisor area, but not for the canine area.…”
Section: Discussionmentioning
confidence: 99%
“…There is no doubt that cone beam computed tomography (CBCT) or medical computed tomography (CT) are the most accurate evaluation techniques and set the gold standard for measurement of bone available for dental implants (16). However, due to lower radiation load and examination cost, panoramic radiography is still considered the standard radiographic examination for implant treatment planning (17).…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Currently, CBCT is being used for a number of applications in dentistry and suggested a useful diagnostic tool. In addition, various studies have concluded that CBCT imaging should be recommended for planning sinus augmentation procedures, [3] however, there is a dearth of studies regarding the comparison between CBCT and panoramic radiography for planning sinus augmentation procedures prior to implant placement in the literature. …”
Section: Introductionmentioning
confidence: 99%